Psychometric Properties of the Form Development of Self-Care Competence of the Person with a Bowel Elimination Ostomy - Pinto, Igor (2016)
Background: The use of an instrument to assess the self-care competence in patients with bowel elimination ostomy allows for the systematic identification of their specific needs, ensuring the continuity of nursing care. Although an instrument that assesses the domains that integrate this competence has been developed in Portugal, it has not yet been validated. Objectives: To assess the psychometric properties of the form Development of Self-Care Competence of the Person with a Bowel Elimination Ostomy. Methodology: Methodological study aimed at analyzing the psychometric properties of a measurement instrument, written in Portuguese. Results: The Cronbach’s alpha was 0.95 and the inter-rater reliability showed a correlation greater than or equal to 0.98. A statistically significant correlation was found in the split-half test, as well as in the clinical sensitivity analysis. Conclusion: The form presented good psychometric indicators, which suggests that it is a useful tool to be used in the nursing diagnosis process, thus contributing to the optimization of nursing care.